Older Adults’ Use of Online and Offline Sources of Health Information and Constructs of Reliance and Self-Efficacy for Medical Decision Making - Hall, Amanda K. (Journal of Health Communication, 2015)
We know little about older adults' use of online and offline health information sources for medical decision making despite increasing numbers of older adults who report using the Internet for health information to aid in patient–provider communication and medical decision making. Therefore we investigated older adult users and nonusers of online and offline sources of health information and factors related to medical decision making. Survey research was conducted using random digit dialing of Florida residents' landline telephones. The Decision Self-Efficacy Scale and the Reliance Scale were used to measure relationships between users and nonusers of online health information. Study respondents were 225 older adults (age range = 50−92 years, M = 68.9, SD = 10.4), which included users (n = 105) and nonusers (n = 119) of online health information. Users and nonusers differed in frequency and types of health sources sought. Users of online health information preferred a self-reliant approach and nonusers of online health information preferred a physician-reliant approach to involvement in medical decisions on the Reliance Scale. This study found significant differences between older adult users and nonusers of online and offline sources of health information and examined factors related to online health information engagement for medical decision making.